Interference Coordination Using Precoding Schemes for Indoor Hotspots - Toha Ardi Nugraha (Journal of Electrical Technology UMY, 2017)
This paper investigates an interference coordination method for indoor hotspot deployment which includes cooperative communication between access points. Coordination between indoor hotspots access point with a method of coordination strategy is used by using of multiple-input multiple-output (MIMO) antennas technique. In order to achieve the capacity, some preceding technique is implemented in MIMO such as Minimum Mean Square Error (MMSE) and Block Diagonalization (BD). MMSE and BD precoding is used to coordinate the transmissions across multiple antenna in transmitter and receiver in case of multiple antenna transmissions. Water-Filling (WF) power allocation is also implemented in this scheme. This schemes is proposed to mitigate inter user interference. Based on the simulation, the results show that coordination scheme in indoor hotspots deployment using BD pre-coding demonstrates a higher data rate than MMSE. The achievable sum rate of hotspot with coordination three access points using BD better around 5 Bps/Hz compared to MMSE method in the same cases.